Evaluation of Integrated Digital Marketing Communication Strategy in the Ministry of Agriculture’s Social Media - Kurnia Saputra, Asep; Handayani, Ridha; Afiah Chusjairi, Juni (Journal Research of Social Science, Economics, and Management, 2026)
This study examines the implementation of integrated digital marketing communication (IMC) within the Ministry of Agriculture’s social media ecosystem in Indonesia. The rapid growth of digital communication has transformed social media from a mere information dissemination tool into a strategic platform for public engagement, institutional branding, and policy communication. However, many government institutions still rely on one-way communication patterns without adapting content to audience characteristics across platforms. Therefore, this study aims to evaluate the Ministry of Agriculture’s social media communication strategy through the four pillars of Integrated Marketing Communication (IMC), namely stakeholders, content, channels, and results. This research employed a mixed content analysis approach combining quantitative-descriptive and qualitative-interpretive methods. The study analyzed 88 posts published across five official social media platforms—YouTube, Instagram, Facebook, TikTok, and X/Twitter—during the observation period from November 27 to December 10, 2025. Interaction metrics, such as likes, comments, shares, views, and engagement rates, were examined to identify communication effectiveness and audience response patterns. The findings reveal that informational content dominated the communication strategy at 61.4%, while educational content was completely absent. TikTok generated the highest interaction despite having fewer followers, indicating that communication effectiveness is strongly influenced by platform-format compatibility rather than audience size alone. The study concludes that the Ministry of Agriculture’s social media has not yet functioned as a fully integrated IMC ecosystem because its communication practices still reflect parallel distribution rather than audience-oriented strategic integration.